proDruck 3D-Druck – Technologie der Industrie 4.0 – als Mittel der Inklusion für Menschen mit Behinderungen in die Arbeitswelt - Kruse, Anne; Müller, Laura; Ott, Manuel; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

3D-Druck – Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Müller, Laura; Ott, Manuel; Jung, Philipp; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons - Li, Jiaxin; Kossmann, Janina; Zeng, Ke; Zhang, Kun; Wang, Bingjie; Weinberger, Christian; Antonietti, Markus; Odziomek, Mateusz; López‐Salas, Nieves (Angewandte Chemie International Edition)
Self-templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m2 g−1) originating from low activity of metal cations (e.g., K+ or Na+) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo-carbons with large SSA of the order of 3000 m2 g−1, pore volume approaching 2 cm3 g−1, tunable oxygen contents, and yields of up to 15 %. We unravel the role of Cs+ as an efficient promoter of framework formation, templating and etching agent, while acetates act as carbon/oxygen sources of carbonaceous frameworks. The oxo-carbons show record-high CO2 uptake of 8.71 mmol g−1 and an ultimate specific capacitance of 313 F g−1 in the supercapacitor. This study helps to understand and rationally tailor the materials design by a still rare organic solid-state chemistry.
Keywords: CO2 Adsorption; Cesium Acetate; Cesium Effect; Porous Carbons; Supercapacitor

TPACK, DPACK, XY-Pack? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Das TPACK-Modell wird häufig zur Konzeptualisierung digitaler Kompetenzen in der Lehrer:innenbildung herangezogen. Es stellt die Bezüge des Lehrer:innenwissens zwischen den Dimensionen des inhaltlichen, pädagogischen und technologischen Wissens her. Wir analysieren in diesem Beitrag die Passung von TPACK zur Modellierung digitaler Kompetenzen für den Kontext der beruflichen Bildung, insb. mit Blick auf die Inhaltsdimension. Wir argumentieren, dass TPACK und solche Modelle, die sich daran anlehnen, den doppelten inhaltlichen Gegenstandsbezug der beruflichen Bildung nicht hinreichend abbilden. Darauf aufbauend diskutieren wir mögliche Weiterentwicklungen des Modells für die berufliche Bildung sowie dessen Bedeutung für die berufliche Lehrer:innenbildung.

Evidenzbasierte Hochschuldidaktik - Scharlau, Ingrid; Jenert, Tobias (Hochschuldidaktik als Wissenschaft: Disziplinäre, interdisziplinäre und transdisziplinäre Perspektiven)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas

Der Einsatz von didaktischen Fallstudien zur Erkundung digital transformierter Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Didaktische Fallstudien zur exemplarischen Erkundung der digitalen Transformation der Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Technological Pedagogical Content Framework for the Vocational Teacher Education in Germany - Sänger, Niklas

Vorstellung eines Trainings zur Förderung des selbstregulierten unternehmerischen Lernens in der Entrepreneurship-Education. - Büker, Ronja; Jenert, Tobias; Fahrbach, Manuel (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias; Kremer, H.-Hugo (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Integrationsgestaltung ausbildungsintegrierender Studienprogramme. Eine theorie- und fallstudienbasierte Analyse - Jenert, Tobias; Mordhorst, Lisa Friederike Anna (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Integrationsgestaltung ausbildungsintegrierender Studienprogramme. Eine theorie- und fallstudienbasierte Analyse - Mordhorst, Lisa Friederike Anna; Jenert, Tobias (Jahrestagung der Gesellschaft für Hochschulforschung)

Jenert, T. & Büker, R. (2023). Designing Self-Regulation interventions for different target groups in Entrepreneurship Education - Jenert, Tobias; Büker, Ronja

Deep neural networks on diffeomorphism groups for optimal shape reparametrization - Celledoni, Elena; Glöckner, Helge; Riseth, Jørgen; Schmeding, Alexander (BIT Numerical Mathematics)

Aspects of control theory on infinite-dimensional Lie groups and G-manifolds - Glöckner, Helge; Hilgert, Joachim (Journal of Differential Equations)
Keywords: 22E65; 28B05; 34A12; 34H05; 46E30; 46E40

Diffeomorphism groups of convex polytopes - Glöckner, Helge (Journal of Convex Analysis)
Let $E$ be a finite-dimensional real vector space and $M\subseteq E$ be a convex polytope with non-empty interior. We turn the group of all $C^∞$-diffeomorphisms of $M$ into a regular Lie group.

Mapping groups associated with real-valued function spaces and direct limits of Sobolev-Lie groups - Glöckner, Helge; Tárrega, Luis (Journal of Lie Theory)

Workload-Aware Periodic Interconnect BIST - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Design &Test)
System-level interconnects provide the backbone for increasingly complex systems on a chip. Their vulnerability to electromigration and crosstalk can lead to serious reliability and safety issues during the system lifetime. This article presents an approach for periodic in-system testing which maintains a reliability profile to detect potential problems before they actually cause a failure. Relying on a common infrastructure for EM-aware system workload management and test, it minimizes the stress induced by the test itself and contributes to the self-healing of system-induced electromigration degradations.
Keywords: Electrical and Electronic Engineering; Hardware and Architecture; Software

Robust Pattern Generation for Small Delay Faults under Process Variations - Jafarzadeh, Hanieh; Klemme, Florian; Reimer, Jan Dennis; Najafi Haghi, Zahra Paria; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE International Test Conference (ITC'23), Anaheim, USA, October 2023)

Simplified numerical calculation of the isothermal, three-dimensional, Non-Newtonian flow characteristics of single-screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Introduction—The Digital Twin of Humans - Gräßler, Iris; Steffen, Eckhard; Maier, Günter W.; Roesmann, Daniel (The Digital Twin of Humans)

The Digital Twin of Humans

Calibration of a Contact Model for DEM Simulations of Grooved Feed Sections of Single Screw Extruders - Schöppner, Volker; Brüning, Florian (36th International Conference of the Polymer Processing Society (PPS-36))

Individual Assembly Guidance - Pöhler, Alexander; Gräßler, Iris (The Digital Twin of Humans)

The short-and long-term properties of welded high-temperature-resistant thermoplastics - Vogtschmidt, Sascha; Schöppner, Volker

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Analysis and modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Altepeter, Matthias; Wanke, Sven; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Integration of Human Factors for Assembly Systems of the Future - Roesmann, Daniel; Gräßler, Iris (The Digital Twin of Humans)

Conceptions and Feasibility Study of Fiber Orientation in the Melt as Part of a Completely Circular Recycling Concept for Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Tölle, Lisa; Greb, C.; Haag, M. (Journal of Composites Science)

Polypropylene Degradation on Co-Rotating Twin-Screw Extruders - Schöppner, Volker; Altepeter, Matthias; Austermeier, Laura; Wanke, Sven; Meinheit, Philipp (Polymers 2023)

Investigation of the Homogenization Performance of Various Faceted Mixers and Optimization with Regard to Mixing as well as Pressure Throughput Behavior - Schöppner, Volker; Frank, Maximilian

Design of a test bench for measuring the degradation behavior of plastics during processing - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (PPS36)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Material Characterization of Polypropylene and Polystyrene Regarding Molecular Degradation Behavior - Schöppner, Volker; Schall, Christoph Wilhelm Theodor (Materials)

Characterization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian (Welding in the World)

POTENTIALS AND GOALS OF MODELS IN STRATEGIC PRODUCT PLANNING AND INNOVATION MANAGEMENT - Gräßler, Iris; Koch, Anna-Sophie; Tusek, Alena Marie (Proceedings of the Design Society)
Abstract New trends and technologies in product creation increase complexity, but at the same time create new potentials such as efficiency rise in task processing by Artificial Intelligence. Established models in the early phase of product creation such as the W-model or the Aachener Innovation Management model, do not fully exploit these new potentials in the field of strategic product planning and innovation management (SPPIM). For this reason, existing models are analysed in SPPIM in order to derive a requirements profile consisting of potentials and goals for a new model. A new model in SPPIM lays the foundation to support companies in enabling a more efficient task fulfilment by taking advantage of new technologies and trends. To guide the development of advanced SPPIM models, the derived potentials and goals are applied to the guideline VDI 2220:1980.

Interdependency study of design guidelines - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Sustainable product life cycle - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Begriffe der strategischen Produktplanung und -entwicklung. Produkt und hybride Leistung - Gräßler, Iris; Ovtcharova, Jivka; Dattner, Michael; Dietert, Tilko; Dietz, Patrick; Elstermann, Matthes; Fayet, Celestin; Hauck, Andreas; Häuser, Frank; Fischer, Holger; Herzog, Michael; Köhler, Christian; et al.

Post-pandemic online mathematics and statistics support: Practitioners’ opinions in Germany and Great Britain & Ireland - Gilbert, H.; Schürmann, M.; Liebendörfer, M.; Lawson, D.; Hodds, M. (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erfassung und Vergleich (mathematischer) Eingangsvoraussetzungen angehender Studierender verschiedener mathematikhaltiger Studiengänge - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Besser, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Zu digital - zu viel - zu schwer? Qualitative Einsichten in das Erleben und Handeln von Erstsemester-Studierenden der Mathematik während der Corona-Pandemie - Kempen, Leander; Liebendörfer, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Bearbeitungsmuster von Studierenden im Umgang mit formalen Definitionen im Kontext konstanter Folgen - Schlüter, Sarah; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Förderung prozeduraler Flexibilität durch Lernvideos mit interaktiven Aufgaben - Krämer, Sandra; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Preservice teachers’ mathematics-related values and expectancy in the transition from school to university
Many preservice mathematics teachers lose their motivation during their first year at university. This phenomenon has been repeatedly described in recent years but is not yet fully understood. Since motivation may relate to different objects such as mathematics or teaching, we aim to qualitatively reconstruct different facets of the central motivational constructs of Situated-Expectancy-Value theory (intrinsic value, attainment value, utility value, cost, and expectancy of success) for preservice mathematics teachers. The analysis of longitudinal group interviews of 14 preservice higher-secondary mathematic teachers from a German university revealed different objects of motivation (e.g., teaching mathematics, scientific mathematics, procedural mathematics, or proof-based mathematics) in preservice teachers' values and expectancy of success. Furthermore, relations between those values and expectancy of success were identified that played a significant role in preservice teachers’ motivational development over their first semester (e.g., relations of attainment value for scientific mathematics and psychological cost). Theoretical and practical implications towards a teaching-specific conceptualization of expectancy of success and values and value interventions are being discussed.

Approach for a sustainable process chain in manufacturing of fasteners for mechanical joining - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson

Determination of Correlations between Melt Quality and the Screw Performance Index in the Extrusion Process - Trienens, Dorte; Schöppner, Volker; Bunse, Robin (Polymers 2023)

Improvement of a method for the correction of wall slip effects within the rheological measurements of filled rubber compounds - Schöppner, Volker; Kleinschmidt, Dennis (SPE Polymers)

Creating Synthetic Training Data for Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc